Analysis of Liquidity, Solvency, and Activity Ratios on the Financial Performance of PT Siantar Top Tbk Listed on the IDX for the Period 2019–2023 - Nur Annisa; Meigia Nidya Sari; Nina Andriany Nasution3 (International Journal of Economic Research and Financial Accounting, 2025)
This study aims to determine the liquidity, solvency, and activity ratios in relation to financial performance at PT. Siantar Top Tbk., which is listed on the Indonesia Stock Exchange (IDX) for the period 2019-2023. The study uses a quantitative descriptive approach with secondary data. Data collection techniques were carried out through documentation and literature studies. Data analysis techniques employed comparative descriptive analysis. The results of the study indicate that financial performance, as measured by liquidity ratios, is in good/inefficient condition, suggesting that the company has a very strong ability to meet its short-term obligations (good). However, the high current ratio exceeding the ideal threshold indicates inefficient utilization of current assets (inefficiency). From the solvency ratio perspective, the company's financial performance is in very good condition, as evidenced by a significant downward trend, thereby reducing dependence on external debt. From the activity ratio perspective, financial performance is in poor condition due to a significant annual decline, reflecting reduced efficiency in utilizing assets to generate revenue.